Adductor canal block combined with genicular nerve block versus local infiltration analgesia for total knee arthroplasty: a randomized noninferiority trial - Tong Mu; Baohong Yuan; Ke Wei; Qian Yang (Journal of Orthopaedic Surgery and Research, 2024)
Abstract Objective This randomized controlled and double-blind study aimed to investigate whether the analgesic effect of the adductor canal block (ACB) combined with the genicular nerve block (GNB) after total knee arthroplasty is noninferior to that of the adductor canal block combined with local infiltration analgesia (LIA). Methods A total of 102 patients undergoing total knee arthroplasty under general anesthesia were included and randomly divided into: ACB + GNB and ACB + LIA groups; the ACB + LIA group received 80 mL of 0.2% ropivacaine with adrenaline 10 µg/mL for LIA, whereas the ACB + GNB group received 4 mL of 0.2% ropivacaine for the blockade of five peri-knee nerves. The primary outcome was the median difference in the visual analog scale scores at rest at 24 h between the two groups. Secondary outcomes involved the median differences in the pain scores at other time points. Other outcomes included the cumulative dosage of opioids calculated in morphine equivalents in the first 24 h and indicators related to knee joint functional recovery. Results In total, 36 and 38 patients were included in the ACB + GNB and ACB + LIA groups, respectively. We found that the median difference (95% confidence internal) in postoperative rest pain at 24 h (noninferiority criteria, △ = 1) was − 0.5 (− 1 to 0, p = 0.002). The median difference in cumulative opioid consumption was 1 mg (− 1 to 3, p = 0.019), meeting the noninferiority criteria, △ = 7.7 mg. Conclusions ACB combined with GNB provides noninferior analgesia compared to ACB with LIA on the first day after total knee arthroplasty while significantly reducing local anesthetic use. Trial registration Name of the Registry: Chinese Clinical Trial Registry; Trial Registration Number: ChiCTR2300074274; Date of Registration. August 2, 2023.